Celiac disease detection rate in gastroenterological patients - S V Bykova; E A Sabelnikova; R B Gudkova; V N Drozdov; P L Shcherbakov; M V Kirova; S G Khomeriki; G G Varvanina; A A Belyaeva; A I Parfenov (Терапевтический архив, 2016)
Aim. To determine celiac disease detection rate in patients with digestive disease. Subjects and methods. A total of 318 gastroenterological patients admitted to be treated at the Central Research Institute of Gastroenterology in September to October 2012 were examined. The patients’ age was 18 to 74 years (mean 51.5±16.4 years). Immunoglobulin A (IgA) and immunoglobulin G (IgG) anti-gliadin antibodies (AGA), IgA anti-tissue transglutaminase (anti-tTG) antibodies and IgG anti-tTG antibodies were determined. When the antibodies were elevated, esophagogastroduodenoscopy with duodenal biopsy was performed. Results. Forty-one of the 318 patients were found to have higher AGA (12.9%); out of them IgA AGA were in 17 (5.35%) patients and IgG AGA were also in 17 (5.35%). Elevated levels of both antibodies (IgA AGA and IgG AGA) were seen in 7 (2.2%) patients. Overall, the detection rate of increased AGA levels was 12.9%. The antibodies were more commonly higher in patients with liver diseases (21.8%) and in those with inflammatory bowel diseases (21.6%). Both IgA anti-tTG, IgG anti-tTG and IgA AGA, IgG AGA were detected in 6 (1.9%) of the 318 patients. The diagnosis of celiac disease was verified by duodenal histological examination in 3 (0.94%) of the 318 patients. Conclusion. The celiac disease detection rate in gastroenterological patients was 0.94%.